Evaluating and Using Literature Including People with Disabilities in All Classrooms - Oslick, Mary Ellen; Pearson, Mary (Journal of the American Academy of Special Education Professionals, 2016)
To help students see their worlds differently and to expand those views beyond their own backyards, educators can expose them to quality multicultural children’s literature. In this article, we focus on a subtopic within the genre of multicultural children’s literature: literature including people with disabilities. We chose seven recent texts that fall under this category to evaluate. To evaluate multicultural literature including people with disabilities, Ramsey’s (2010) reader criteria were used. Finally, we share three distinct techniques with suggestions for incorporating these texts: reciprocal teaching, literature circles, and critical literacy strategies. These practices can help teachers use the previously reviewed texts effectively in their classrooms.